Sustainability Matters Prospects for a Just Transition in Calgary, Canada's Petro-City - Keough, Noel (University of Calgary Press, 2021)
Calgary, Alberta is a culturally diverse urban metropolis. Sprawling and car-dependent, fast-growing and affluent, it is dominated by the fossil fuel industry. For 30 years, Calgary has struggled to turn sustainability rhetoric into reality. Sustainability Matters is the story of Calgary's setbacks and successes on the path toward sustainability. Chronicling two decades of public conversations, political debate, urban policy and planning, and scholarly discovery, it is both a fascinating case study and an accessible introduction to the theory and practice of urban sustainability. A clear-eyed view of the struggles of turning knowledge into action, this book illuminates the places where theory and reality converge and presents an approach to municipal development, planning, and governance that takes seriously the urgent need to address climate change and injustice. Addressing a wide variety of topics and themes, including energy, diversity, economic development, and ecological health, Sustainability Matters is both a critique of current practice and a vision for the future that uses the city of Calgary as a microcosm to address issues faced by cities around the world. This is essential reading not only for every Calgarian working for a vibrant and sustainable future, but for all those interested in in the future of cities in a post-carbon world.